Library Curriculum as Epistemic Justice: Decolonizing Library Instruction Programs - Campbell, Heather; Sich, Dan (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
Information literacy scholars and leaders are calling for the decolonization of library instruction, knowing that our work helps to maintain colonial systems. While there is no checklist or road map to program decolonization, academic libraries and instruction teams must start the work anyway. This article shares the story of curriculum decolonization at Western Libraries, so far, including the decolonization ‘cycle’ we followed and our resulting six learning outcomes. Grounded in epistemic justice, our new curriculum prioritizes living beings over information, and uses a broad, inclusive definition of knowledge throughout. Librarians at Western University acknowledge that the first step in decolonization is making space for multiple ways of knowing and that white librarians have particular responsibilities within this work to decolonize their minds. While our curriculum is far from perfect, we invite other educators to use and adapt our learning outcomes, as well as the decolonization approach and reflection questions shared here.